Effectiveness of Maranti Stimulation in Improving Growth and Development Among Stunted Toddlers: A Quasi-Experimental Study - Dewi Rokhanawati; Nidatul Khofiyah; Elika Puspitasari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Stunting remains a major public health concern in Indonesia, particularly during the first 1,000 days of life, and reflects the cumulative effects of nutritional deficits, infection, and suboptimal caregiving within broader social and environmental conditions. This study draws on current national and global evidence to frame stunting as a developmental and ecological problem that requires integrated, family-centred interventions. This study aimed to assess the effectiveness of Maranti stimulation (massage therapy for stunting), in enhancing growth and development among stunted children. Methods: This quasi-experimental study utilized a non-equivalent control group design and was conducted from August to November 2024 at two public health centers in Bantul, Yogyakarta, Indonesia. Participants were divided into two groups: the intervention group (n=23), which received weekly Maranti massage sessions over six weeks, and the control group (n=25), which was provided with educational booklets on child growth and developmental stimulation. Growth measurements were collected using anthropometric tools, and developmental outcomes were assessed using the BSID-III instrument. Data normality was assessed prior to analysis. Normally distributed variables were analyzed using independent t-tests, while non-normally distributed variables were analyzed using the Mann–Whitney U test in Stata. Results: The findings revealed significant improvements in growth and development post-intervention in both groups, with more pronounced effects in the intervention group. Notably, Maranti therapy significantly increased body weight (p=0.016) and height (p=0.001). Language (p=0.025) and motor skills (p=0.045) also improved significantly. Cognitive development, however, did not show a statistically significant change (p=0.635). Effect size analysis indicated medium to strong effects for weight and height (Cohen’s d = 0.724 and 1.041), and moderate effects for language and motor development (Cohen’s d = 0.580 and 0.595). Conclusion: Maranti stimulation demonstrates promise as an effective complementary strategy to improve physical growth and developmental outcomes in stunted children, though further research is needed regarding cognitive impacts. These findings suggest that culturally embedded tactile stimulation can serve as a feasible complementary approach for growth-promotion programs. The intervention holds potential for integration into community-based stunting-reduction strategies, particularly in settings where traditional practices remain influential.